2018
DOI: 10.1158/1535-7163.mct-17-1204
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-derived Xenograft Model of Pancreatic Neuroendocrine Tumors Identifies Sapanisertib as a Possible New Treatment for Everolimus-resistant Tumors

Abstract: Patients with pancreatic neuroendocrine tumors (PNETs) commonly develop advanced disease and require systemic therapy. However, treatment options remain limited, in part because experimental models that reliably emulate PNET disease are lacking. We therefore developed a patient-derived xenograft model of PNET (PDX-PNET) which we then used to evaluate two mTOR inhibitor drugs: FDA-approved everolimus and the investigational new drug sapanisertib. PDX-PNETs maintained a PNET morphology and PNET-specific gene exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 57 publications
(71 reference statements)
0
29
0
Order By: Relevance
“…However, as complete responses to LuTate are rare, novel approaches are needed to further potentiate its clinical activity. Preclinical efficacy studies are of great value for evaluating novel treatments but the lack of robust and well validated preclinical models of SSTR2-expressing NET available for the assessment of novel combination regimens incorporating SSTR2 targeted PRRT is well documented [40][41][42] . In this study, we therefore characterised a panel of cell lines with neuroendocrine features to identify a line suitable for such studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, as complete responses to LuTate are rare, novel approaches are needed to further potentiate its clinical activity. Preclinical efficacy studies are of great value for evaluating novel treatments but the lack of robust and well validated preclinical models of SSTR2-expressing NET available for the assessment of novel combination regimens incorporating SSTR2 targeted PRRT is well documented [40][41][42] . In this study, we therefore characterised a panel of cell lines with neuroendocrine features to identify a line suitable for such studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Nölting et al showed that combination of everolimus and BYL719 had synergistic effects on cell proliferation (Nölting et al 2017). In addition, combination of BYL719 with everolimus re-established everolimus sensitivity in a resistant cell line model (Aristizabal Prada et al 2018 (Chamberlain et al 2018). They show that sapanisertib overcomes everolimus resistance.…”
Section: Dual Pi3k and Mtor Inhibitorsmentioning
confidence: 91%
“…PDXs of pancreatic NEN can develop resistance to everolimus. In this study, the inhibitor of the mTOR pathway sapanisertib showed a potent antitumor effect also on everolimus-resistant PDXs, leading to the suggestion of a new alternative pharmacological strategy for everolimus-resistant NEN (71). However, the use of murine NEN-PDX models is very limited in the research of PM strategies probably due to the rarity of NENs, the limited size of post-surgical samples for most of these tumors and the low rate of successful tumor engraftment (72).…”
Section: In Vivo Modelsmentioning
confidence: 86%